MODEL AKAD QARDHUL HASAN PADA USAHA MIKRO KECIL MENENGAH - Rini Rahayu Kurniati; Afifuddin ,; Sri Nuring Wahyu (Akutansi Bisnis & Manajemen ( ABM ), 2020)
The purpose of the research was to analyze the qardhul hasan contract model in small and medium entrepreneurs (MSMEs) in the context of economic development in Batu City and to analyze the role of the qardhul hasan contract in small and medium entrepreneurs (MSMEs) in the context economic development in Batu City. This research uses qualitative descriptive method by collecting data using analytical technical triangulation through head micro unit of Sharia BRI Batu City and qarhul hasan customers as informans. The results showed that the qardhul hasan contract model was in the form of: a contract based on sharia concept, namely the provision of loan funds for businesses based on customers who needed and paid back according to ability. The role of the qardhul hasan contract is to create a sense of independence, create creativity to start and develop a business.